Analysis of Figurative Language in “Rewrite the Stars” Song Lyrics - Erni Putri Suriyani Bawemenewi; Ni Wayan Swarniti (PRAGMATICA : Journal of Linguistics and Literature, 2024)
It is important to analyze the use of figurative language in song lyrics. That is why the researcher wants to examine figurative language more thoroughly, especially in the song "rewrite the stars" Therefore, this research will concentrate on the figurative language and the context of song lyrics. The present study employed the qualitative method in order to examine more thoroughly and solve problems in this review. The researchers collect data from several sources, i.e., journals, the internet, or other written sources. It was concluded as follows: In Comparative Figurative Language, was found data in simile, personification, and Metaphor. The personification found was 1 data. In Contradictive Figurative Language, it was found litotes, irony, and paradox. The only one Contradictive Figurative Language that was not found. It was hyperbole. The data of litotes was 1 data. the data of irony was 1 data. The data of paradox was 1 data. In Correlative Figurative Language, there are four kinds. The data of allusion was 1 data. The data of ellipsis was 1 data. The data of allusion was 1 data. this data also has a symbol in figurative language. The word "stars" in sentence "rewriting the stars" has a symbol as relationship. So that is why this data classified as symbol in figurative language. The data of metonymy was 1 data, and the data of synecdoche was 1 data. Based on the result analysis, this song lyric had many figurative languages. It means this song lyric tried to use figurative language to express the feeling or idea imaginatively. In other word, this song lyric tried to create a special image and bring out one's emotions.